MONITORING CAHAYA, SUARA, SUHU, DAN KELEMBABAN PADA RUANG PEMBELAJARAN BERBASIS MIKROKONTROLER - Selviani, Tri Novi Widya; Wahyono, Unggul (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
The purpose of this research is to make a measuring instrument for light, sound, temperature, and humidity in a learning room based on a microcontroller that is integrated into one. This research is a type of research and development or known as R&D (Research and Development) which refers to the ADDIE development model which includes the Analysis, Design, Development, Implementation stages. This measuring instrument is made using the Arduino ESP32 module which is programmed using the Arduino programming language. After validation and revision, the product that has been developed is tested. The instrument used was a questionnaire with a Likert scale which was shown to media experts and physics teachers. Based on data analysis shows that, media expert validation the average score of tool quality is 3.93 with the "Very Good" category, the teacher's response at SMAN 2 Palu shows an average score of 3.87 in the "Very Good" category and 4.00 with "Very Good" category, SMAN 4 Palu showed an average score of 3.06 in the "Good" category and 3.37 in the "Very Good" category, SMAN 7 Palu showed an average score of 3.75 in the "Very Good" category and 3.87 with the category "Very Good". Based on the results of the study indicate that the measuring instrument that has been developed is feasible to use.